PERFORMATIVE PEDAGOGIES AND EMBODIED EPISTEMOLOGIES: REIMAGINING THEATRE ARTS WITHIN THE PARADIGM OF NATIONAL EDUCATION POLICY 2020 - DR. KIRAN KUMAR SANGALA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This research paper interrogates the transformative potential of Theatre Arts within the educational vision of National Education Policy 2020 through the conceptual lens of performative pedagogy and embodied epistemology. It argues that theatrical praxis functions as a dynamic pedagogical instrument fostering experiential cognition, cultural literacy, affective intelligence and dialogic learning. By integrating indigenous performance traditions, interdisciplinary methodologies and practice-based learning frameworks, this study repositions Theatre Arts as a critical epistemic domain within holistic education. This paper further examines how performative learning dismantles rigid pedagogic hierarchies and cultivates creative, participatory and culturally responsive educational ecosystems.